ORIGINEA NATURII UMANE, FUNDAMENT PENTRU DREPTURILE OMULUI (Journal for Freedom of Conscience (Jurnalul Libertății de Conștiință), 2022)
The origin of human nature, the foundation for human rights.Human rights are presented to us today as a mark of modernity, being perceived more as a politico-social concept and less as a consequence of what the specific man has in his being and which makes him unique in relation to the whole created world. No one can think and act today outside of these true matrices of thought, which offer the simplest way to understand human dignity and the freedom on which it is based, without the need for any theological or philosophical argument. No one can deny that human rights oppose the theological vision of man, created by God, the natural „sacred, inalienable and imprescriptible” right of man, who claims his freedoms in relation to himself and to the nature of which he is a part. However, the fact that human civil rights have a foundation in natural law can open the perspective of the theological argumentation of natural rights, which derives primarily from the quality of man as a being created by God, whose origin is clearly superior to everything that is created. That is why a reflection on the theological arguments that ontologically grounded the human rights, based on the concept of freedom and that of the person. It is more than necessary to understand the spirit of true freedom in which the man lives and moves.